(untitled) - Singh, S. K. (Laxmi Nagar, Delhi, 2002)
Contents of material: Automated library. Automated acquisitions. Integrated online system. Data integraty and technical services. Serials and infoage cataloguing. Information security. Preservation. Information retrieval. Information evaluation.
Keywords: Library science,Library administration